Molecular Diagnosis of Hemoparasitis in dogs attended at the Veterinary Hospital of the Universidade Santo Amaro, São Paulo, SP, Brazil - Silva-Junior, Edilson (2021)
OBJETIVO: Detecção de Ehrlichia canis, Rickettsia rickettsii, Anaplasma platys, Rangelia vitallii, Babesia canis vogeli por meio de PCR em tempo real em cães atendidos no hospital veterinário da Universidade Santo Amaro, localizado na zona sul, do município de São Paulo, SP, Brasil. MÉTODOS: Foi realizada extração de DNA de 63 amostras de sangue total pelo “kit” de extração “PureLink Genomic DNA Kit” (Invitrogen®) conforme instruções do fabricante e realizada a PCR em tempo real para a detecção de Ehrlichia canis, Rickettsia rickettsii, Anaplasma platys, Rangelia vitallii, Babesia canis vogeli. RESULTADOS: 23,8% (15/63) das amostras foram positivas na PCR em tempo real para pelo menos um agente patogênico. Destas, 9,52% (6/63) foram positivas para Babesia canis vogeli e 14,2% (9/63) para Ehrlichia canis.  Nenhuma amostra foi positiva para Rickettsia rickettsii, Rangelia vitalli e Anaplasma platys. CONCLUSÃO: Este estudo demonstrou a presença de B. canis vogeli e E. canis em cães de áreas de fragmentação de Mata Atlântica aos arredores da represa Guarapiranga da cidade de São Paulo de maneira inédita, ampliando o conhecimento da dispersão desse agente no país. DESCRITORES: Ehrlichia canis, Rangelia vitalli, Babesia canis vogeli, Rickettsia rickettsii, Anaplasma platys. ABSTRACT OBJECTIVE: Detection of Ehrlichia canis, Rickettsia rickettsii, Anaplasma platys, Rangelia vitalii, and Babesia canis vogeli using real-time PCR in dogs treated at the veterinary hospital of the Universidade Santo Amaro, located in the south zone, in the city of São Paulo, SP, Brazil. METHODS: DNA was extracted from 63 whole blood samples using the “PureLink Genomic DNA” extraction kit (Invitrogen®) according to the manufacturer's instructions and real-time PCR was performed to detect Ehrlichia canis, Rickettsia rickettsii, Anaplasma platys, Rangelia vitalii, and Babesia canis vogeli. RESULTS: In total, 23.8% (15/63) of the samples were positive by real-time PCR for at least one pathogen. Of these, 9.52% (6/63) were positive for Babesia canis vogeli and 14.2% (9/63) for Ehrlichia canis.  No samples were positive for Rickettsia rickettsii, Rangelia vitalii, and Anaplasma platys. CONCLUSION: This study demonstrated, in an unprecedented way, the presence of B. canis vogeli and E. canis in dogs from fragmentation areas of the Atlantic Forest around the Guarapiranga Reservoir in the city of São Paulo, expanding knowledge on the dispersion of this agent in Brazil. DESCRIPTORS: Ehrlichia canis, Rangelia vitalii, Babesia canis vogeli, Rickettsia rickettsii, Anaplasma platys.